The Influence of Influencer Affiliate Marketing Strategies on Generation Z's Purchasing Decisions: An Analysis of Business Communication on the TikTok Platform - Zidnal Falah; Naufal Hadi Makarim; Muhammad Irsyad Sabiq; Ferry Darmawan (International Journal Labs, 2025)
This study aims to analyze the influence of affiliate marketing strategies carried out by influencers on Generation Z's purchasing decisions on the TikTok platform. Through a qualitative approach with a case study method, data was collected through in-depth interviews with 10 TikTok influencers, questionnaires of 50 Generation Z respondents, content observation, and analysis of related documents. The results show that trust in influencers, content quality, and special offers (such as discounts) are the dominant factors influencing Generation Z's purchasing decisions. Authentic, entertaining, and informational content—such as tutorials or product reviews—has been shown to be more effective in increasing audience engagement than conventional promotions. These findings are in line with previous research that emphasized the importance of transparency and social proof in digital marketing, but this study enriches the literature with a specific focus on the mechanism of affiliate marketing on TikTok. The practical implications of this study include recommendations for businesses to choose influencers that are relevant to the target market, increase content transparency, and take advantage of economic incentives. For academics, this research provides a new perspective on the dynamics of business communication on short content-based social media platforms. The study's main limitation lies in its limited scope on TikTok and Generation Z, so further research is needed to compare the effectiveness of similar strategies on other platforms or different generations.